Etika Birokrasi dan Kultur Masyarakat di Indonesia - Delly Mustafa (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2012)
Abstract A long way in history has showed us proof that bureaucracy in Indonesia is so far away from expectation of most Indonesian people. After sixty seven (67) years of independent state through three orders (old order, new order, and reformation order), especially within this reformation order, we really should have been free from the gloomy shadows of misleading bureaucracy. And yet now we're not. However, the important role of bureaucracy in Indonesia doesn't automatically show a good portrait of good bureaucracy. In people's perception, there's still a lot of works to do to improve the image and performance of our bureaucracy. People generally don’t like to face bureaucracy. The word